2020
DOI: 10.1210/jendso/bvz038
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Newer Concepts of Its Metabolism and Function at the Basic and Clinical Level

Abstract: The interest in vitamin D continues unabated with thousands of publications contributing to a vast and growing literature each year. It is widely recognized that the vitamin D receptor (VDR) and the enzymes that metabolize vitamin D are found in many cells, not just those involved with calcium and phosphate homeostasis. In this mini review I have focused primarily on recent studies that provide new insights into vitamin D metabolism, mechanisms of action, and clinical applications. In particular, I examine how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 183 publications
0
99
0
7
Order By: Relevance
“…Vitamin D metabolism involves three steps, including 25-hydroxylation, 1α-hydroxylation, and 24-hydroxylation, that are performed by cytochrome P450 mixed-function oxidases (CYPs) [47]. Recent studies showed that the regulation of these vitamin D metabolizing enzymes may relate to vitamin D metabolism and further play a potential role in enhancing the regulation of metabolic processes [48]. The cholesterol side-chain cleavage enzyme (CYP11A1), which catalyzes the first step in steroidogenesis, has been found to involve in the sequential hydroxylation, predominantly at C-20 or C-22, in the vitamin D metabolism [49].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D metabolism involves three steps, including 25-hydroxylation, 1α-hydroxylation, and 24-hydroxylation, that are performed by cytochrome P450 mixed-function oxidases (CYPs) [47]. Recent studies showed that the regulation of these vitamin D metabolizing enzymes may relate to vitamin D metabolism and further play a potential role in enhancing the regulation of metabolic processes [48]. The cholesterol side-chain cleavage enzyme (CYP11A1), which catalyzes the first step in steroidogenesis, has been found to involve in the sequential hydroxylation, predominantly at C-20 or C-22, in the vitamin D metabolism [49].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is ingested from plant (D2) or animal (D3) sources including dairy products (often vitamin fortified) and fish. Vitamin D is also synthesized when 7-dehydrocholesterol in the skin is converted to cholecalciferol upon exposure to sunlight (ultra violet B (UVB)) rays) [67]. In the liver, Debates continue as to the appropriate levels of vitamin D in blood, but most scientists agree that blood levels of >30 ng/mL vitamin D will support a healthy immune system.…”
Section: Vitamin D and The Immune Responsementioning
confidence: 99%
“…Vitamin D is ingested from plant (D2) or animal (D3) sources including dairy products (often vitamin fortified) and fish. Vitamin D is also synthesized when 7-dehydrocholesterol in the skin is converted to cholecalciferol upon exposure to sunlight (ultra violet B (UVB)) rays) [ 67 ]. In the liver, 25-hydroxylase converts cholecalciferol to 25 hydroxy-vitamin D (25(OH)D, also termed calcidiol), a common metabolite in the blood.…”
Section: Vitamin D and The Immune Responsementioning
confidence: 99%
“…Collectively, these findings suggest that total 25(OH)D, while relevant, may not be suitable as a single measure to adequately reflect functional vitamin D status in certain conditions, including in pregnancy [ 23 ]. To further clarify the relationship between maternal vitamin D status and neonatal outcomes, measurement of free and bioavailable metabolites should be considered, particularly given the elevated concentrations of VDBP in the pregnant state.…”
Section: Introductionmentioning
confidence: 99%